R.S. Thomas: poetry and theology - Davis, William Virgil (Baylor University Press, 2007)
This volume celebrates the work of the Welsh poet R. S. Thomas (1913-2000) and illuminates the theological implications of this famous twentieth-century poet-priest's pilgrimage. By providing detailed readings of individual poems, Davis explores the depth and imagination of Thomas's profound theological vision